Driven - Zanetti, Rebecca (Zanetti, Rebecca. Deep ops series., 2021)
On the hunt for a serial killer called "the Surgeon," Angus Force is teamed up with Deep Ops Unit psychiatrist Nari Zhang and the attraction between them is as dangerous as the killer.